RANCANG BANGUN DAN PENGUJIAN DEVAIS PERIPHERAL INPUT/OUTPUT (P I/O) BERBASIS UNIVERSAL SERIAL BUS (USB) - Agus Pracoyo; Tossin Alamsyah (Politeknik Negeri Jakarta, 2011)
Almost all modern computers provide a USB port (Universal Serial Bus) for access to the device input / output external. This phenomenon has forced the designers and developers full-custom devices, input / output is always based on the USB interface technique. A USB system consists of a controller (host PC) and several Device input / output This research aims to design devices, input / output USB HID class (Human Interface Decive). Design based on the USB protocol version 1.1 and 2.0 as the software on the Device (firmware) and the host, as a controller selected PIC18F4550 microcontroller. The design of devices, input / output USB with analog and digital terminals that can diakes and controlled by the host Testing is done using software USBTrace. The test results showed that the speed of transactions is achieved is 12 Mbps (full-speed) with 48 MHz MCU clock Key words: Design, Testing, Peripheral Input Output (PI/O) , Universal Serial Bus (USB) ABSTRAK Teknologi Personal Computer (PC) telah menyediakan terminal USB (Universal Serial Bus) untuk keperluan akses dari dan ke devais input/output eksternal. Fenomena ini memaksa para perancang dan pengembang full-custom untuk merancang devais input/output berbasis antar muka USB. Sistem USB terdiri dari pengontrol yaitu PC sebagai host dan beberapa devais input/output (I/O) sebagai client. Pada artikel ini dibahas hasil rancangan dan pengujian devais input/output Human Interface Decive USB dengan Microcontroller PIC18F4550. Pengujian menggunakan software Tools USBTrace yang dikembangkan oleh SysNucleus. Hasil pengujian menunjukkan bahwa kecepatan transaksi dapat mencapai 12 Mbps, merupakan kategori full-speed. Kecepatan Transaksi dicapai berdasarkan pada Compiler MikroC, dengan clock pada MCU 48 Mhz dan xtal terpasang 8 Mhz. Kata Kunci: Rancang bangun, Pengujian, Peripheral Input Output (PI/O) , Universal Serial Bus (USB)